IMPLEMENTATION OF COMMUNITY-BASED TOTAL SANITATION POLICY BY VILLAGE OFFICIALS IN REALIZING HEALTHY CARE VILLAGES IN BOJONGMALANG VILLAGE CISAGA DISTRICT CIAMIS REGENCY - Vira Nadia Komara; Aditiyawarman; Candra Pirmanto (JGSRD: Journal of Government Science and Rural Development, 2020)
The background of this research is that there are people who do not care less about the health of the community environment. Example: Liquid waste that pollutes the environment of residents, resulting in various unpleasant odors and has a negative impact. The lack of family latrines that do not meet the requirements can be seen from the Family Card data. Example: In the use of latrines, the use of toilets and Spitenk is supposed to be used, but some still use Septic Tank and open space. There are still residents who litter their household waste carelessly, causing various diseases. Example: Inorganic and non-organic waste management should be separated and reused. The method used is descriptive qualitative, with the results of the research that the implementation of community-based total sanitation policies in realizing a healthy caring village in Bojongmalang Village, Cimaragas District, Ciamis Regency. The obstacles faced are low human resources; The difficulty of integrating perceptions in the process of implementing a community-based total sanitation policy in realizing a healthy caring village so that people do not understand and ignore awareness of hygiene and health. Efforts made to overcome obstacles are to improve community human resources; improve education, provide socialization, optimize teams, provide direction and foster enthusiasm between governments, especially the community so that the program objectives are achieved which consists of 5 pillars of Community-Based Total Sanitation including; Stop open defecation, wash hands with soap, manage drinking water and household food, manage household waste, manage household liquid waste.